IEEE sensors 2016 poster - Barrington, James; James, Stephen W.; Tatam, Ralph P.; Partridge, Matthew (Cranfield University, 2016)
Conference poster for IEEE sensors 2016 conference. Data can be found using the referenced URL.
Keywords: Poster'; 'Long period gratings'; '2nd order coupling'; 'Optical Physics not elsewhere classified'